2008
DOI: 10.1097/qad.0b013e32830bfed8
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus 2 serostatus and viral loads of HIV-1 in blood and semen as risk factors for HIV transmission among men who have sex with men

Abstract: Objective Human immunodeficiency virus type 1 blood plasma viral load is correlated with the sexual transmission of HIV, although transmission from men involves virus from semen instead of blood. We quantified HIV-1 RNA in the blood and semen of men who did or did not transmit HIV to their sex partners. We compared the relationships of HIV-1 transmission risk with blood plasma viral load, seminal plasma viral load, herpes simplex virus 2 serostatus and other factors. Design A case–control study. Methods Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 26 publications
2
43
0
Order By: Relevance
“…(i) Overall. Similar to previous studies (13,39,56,69,72), we found a positive trend between HIV RNA levels in blood and semen (P ϭ 0.07), while no correlations were found between seminal HIV and CMV levels (P ϭ 0.35) or between seminal HSV and CMV levels (P ϭ 0.39). Activation levels (RA-CD38 ϩ ) of CD4 ϩ and CD8 ϩ subsets in blood were highly correlated with each other (P Ͻ 0.001) and with activation of CD8 ϩ T cells in semen (P Ͻ 0.01).…”
Section: Study Participantssupporting
confidence: 90%
See 3 more Smart Citations
“…(i) Overall. Similar to previous studies (13,39,56,69,72), we found a positive trend between HIV RNA levels in blood and semen (P ϭ 0.07), while no correlations were found between seminal HIV and CMV levels (P ϭ 0.35) or between seminal HSV and CMV levels (P ϭ 0.39). Activation levels (RA-CD38 ϩ ) of CD4 ϩ and CD8 ϩ subsets in blood were highly correlated with each other (P Ͻ 0.001) and with activation of CD8 ϩ T cells in semen (P Ͻ 0.01).…”
Section: Study Participantssupporting
confidence: 90%
“…uman immunodeficiency virus 1 (HIV) RNA viral loads in blood (31,59) and semen (7,13) of HIV-infected individuals correlate with the risk of sexual transmission (15,28,44). Although HIV RNA levels in blood roughly correlate with levels in seminal plasma (13,39,56,69,72), local genital factors, particularly concomitant sexually transmitted infections (STI), can increase HIV shedding in semen (38,39,61).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al (2010) reported that the probability of unprotected heterosexual transmission may vary with population and be influenced by many factors, these could include: the type of sex (Mastro et al, 1994: De Vincenzi, 1994Varghese et al, 2002); bleeding during intercourse (Royce et al, 1997), semen viral load (Gupta et al, 1997;Tachet et al, 1999;Kalichman et al, 2008;Butler et al, 2008), stage of HIV infection (Mastro et al, 1994;Fauci et al, 1996;Wawer et al, 2005), comorbid sexually transmitted diseases (Royce et al, 1997), vaginal or anal canal, co-occurring psychosocial risk factors . Sexual forms of transmission are seen as a major portal of entry of HIV as 10-30% of seminal/vaginal fluids have transmissible virus (Royce et al, 1997;Henin et al, 1993).…”
Section: Horizontal (Heterosexual) Transmissionmentioning
confidence: 99%